(untitled) (Revista Iberoamericana de Bioética, 2018)
The process of medicalization has an unquestionable impact on everyday life, particularly on the populations of the countries that are large consumer markets of medicines and health resources. The present study consists of theoretical research which aims to analyze the interface between medicalization and human rights of patients. It draws the conclusion that the process of medicalization has a direct impact on the exercise of human rights by the patients. In addition, it verifies that the medicalization process guided by the logic of market is strong and difficult to restrain, therefore, it is imperative that the State adopts a law on patients’ human rights.